Identification of Plasmepsin Inhibitors as Selective Antimalarial Agents using Ligand Based Drug Design - DEMPSEY, ENDA; LLOYD, DAVID G; CARTA, GIORGIO; FAYNE, DARREN; BELL, ANGUS (Elsevier, 2011)
We describe the application of Ligand Based Virtual Screening technologies towards the discovery of novel Plasmepsin (PM) inhibitors, a family of malarial parasitic aspartyl proteases. Pharmacophore queries were used to screen vendor libraries in search of active and selective compounds. The virtual hits were biologically assessed for activity and selectivity using whole cell Plasmodium falciparum parasites and on target in PM II, PM IV and the closely related human homologue, Cathepsin D assays. Here we report the virtual screening highlights, structures of the hits and their demonstrated biological activity.
PUBLISHED
Keywords: Biochemistry; Ligand based drug design